Factores socioculturales que influyen en la participación del servicio de acompañamiento a familias del Programa Nacional Cuna Más en Bagazán, provincia de Requena 2021 - Guerra Ruiz, Diana Stefani (2022)
This research addresses as a central problem: What are the sociocultural factors that influence the participation of user mothers in the family support service of the Cuna Mas national program in the town of Bagazán, province of Requena 2021? The general objective is to determine the sociocultural factors that influence the participation of user mothers in the support service for families of the Cuna Mas national program in the town of Bagazán, province of Requena 2021, the qualitative approach was used, which it reflects the daily life of the population involved, the context and the socio-cultural dynamics. Likewise, it is descriptive and ethnographic in design. The population is a total of 1000 inhabitants and as a sample 60 user mothers. It had as techniques the semi-structured interview and participant observation. The research concludes by explaining that the level of participation of the users in the meetings is low, because they are dedicated to the farm, household chores and commerce, regarding compliance with the guidelines is minimal, because there is no active participation. and because they consider that it does not fit their context. The social factors that influence participation are associated with the ways of raising children, the poor education of the users, as well as the weak relationship that exists in the community, between families and with the facilitators. It is important to know the cultural factors that influence the participation of traditional knowledge of caring for children, which maintain a worldview inherited from parents and is associated with traditional health, language and traditional clothing that modernity has been neglecting (weakening the cultural identity, food based mainly on the food provided by the farm and fishing). Finally, regarding the perceptions about the program, they consider that the initiative is important; however, they request greater understanding about their work and good treatment for their involvement.